Is Fidelity Ethical? The Social Role of the Healthcare Interpreter - Clifford, Andrew (TTR, 2004)
AbstractThis article explores the conduit model so often promoted in community interpreting and its connection with ethical behaviour. The author begins by exploring the origin of the model and the pathways through which it came to be applied in community interpreting. He then considers the model against the backdrop of competing ethical approaches and questions why it continues to be promoted in the face of mounting evidence of its shortcomings. Finally, he presents new information derived from interviews with stakeholders in the healthcare sector. The author argues that this information indicates practitioners may be willing to work with interpreters who take on a wider role, and he concludes by underlining the need to recognize the complexity in the work interpreters do.